2018
DOI: 10.1002/tesq.485
|View full text |Cite
|
Sign up to set email alerts
|

Online Media Creation and L2 Motivation: A Socially Situated Perspective

Abstract: Digital technologies are increasingly common in language learning. Online media creation provides scope for agency and spaces for identity construction, but empirically grounded conceptualizations of the influences on learners' motivation are lacking and the digital technology-second language motivation interface remains largely unexplored. Using a grounded theory ethnographic approach (Charmaz, 2006), and with the aim of developing a theoretical account of the emergence of motivation in online media creation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…For example, in a project focusing on poetry, students created a dedicated Facebook group where they shared work in progress, and received peer feedback (Henry & Thorsen, 2019). In a project where students blogged about an imaginary journey to an English-speaking country on openly accessible websites, students monitored each others' work (Henry, 2019). When, for example, one group decided to include a video containing bloopers alongside an ‘official’ vlog, several other groups followed suit.…”
Section: Exploring Connections With Working Approaches and Influences On Students' Engagementmentioning
confidence: 99%
“…For example, in a project focusing on poetry, students created a dedicated Facebook group where they shared work in progress, and received peer feedback (Henry & Thorsen, 2019). In a project where students blogged about an imaginary journey to an English-speaking country on openly accessible websites, students monitored each others' work (Henry, 2019). When, for example, one group decided to include a video containing bloopers alongside an ‘official’ vlog, several other groups followed suit.…”
Section: Exploring Connections With Working Approaches and Influences On Students' Engagementmentioning
confidence: 99%
“…In the observations carried out in the MoTiSSE project, teaching often centered around activities that provided students with opportunities for creativity and personal expression (Henry, 2019; Henry & Thorsen, 2018a, 2018b, 2019; Henry et al, 2018). Working with these activities, students would frequently demonstrate high levels of engagement, often for sustained periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…The second case (‘Visting India’) occurred in a project where 7th grade students created a blog about an imaginary trip to an English-speaking country and, during lessons, worked together in writing posts about events taking place on different days of the journey (Appendix 2). In both activities, motivational affordances included scope for autonomy, the triggering of imagination, and the use of digital resources to create aesthetically appealing textual artefacts (Henry, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop an understanding of the responsiveness theorized to be characteristic of successful motivators (Lamb, 2017), classrooms where relationships are positive, where students are motivated, and where teachers are aware of and interested in students' lives and experiences outside school provide suitable sites for research. Here we draw on data collected in a 9th grade class as part of the Motivational Teaching in Swedish Secondary English (MoTiSSE) project (Henry, 2018;Henry, Korp, Sundqvist, & Thorsen, 2018;Henry & Thorsen, 2018a, 2018b, 2018cHenry, Sundqvist, & Thorsen, 2019). Ethnographic research was conducted in the classrooms of 16 teachers identified from a randomly-drawn sample (N = 252) as being knowledgeable about and interested in students' out-of-school activities involving English, possessing a professional practice informed by these insights, and having students who were generally motivated.…”
Section: Methodsmentioning
confidence: 99%